The Collaborative Role of the Presbyteral Council in Diocesan Governance in Law and Statutes - Okosun, John E. (Studia canonica, 2013)
The study explores the role of the presbyteral council as an organism of collaboration in the governance of the diocese. The A. explains the current law on the presbyteral council, stressing that its statutes are important instruments for the realization of the goals of the council. He analyses the statutes of twenty-nine North American archdioceses and makes recommendations so that they are faithful to the universal law and more effective guides for the functioning of the council and for fostering its collaborative role in the governance of the local Church.